MENANAMKAN NILAI TOLERANSI MELALUI SEMINAR MODERASI BERAGAMA DI MA MAZRA’ATUL ULUM PACIRAN - Rifa’i, Ahmad Suzaki; Maskanah, Ulfa; Fadilillah, Tegar Adlu; Nuriyah, Addina Silky (Muta'allim: Jurnal Pendidikan Agama Islam, 2024)
This article discusses the implementation of religious moderation through a seminar held at Mazra'atul Ulum Paciran Islamic Senior High School (MA). The seminar aims to enhance participants' understanding of the values of tolerance and moderation in the context of religious diversity in Indonesia. Using a qualitative approach, the seminar involved all MA students as well as school stakeholders in discussions and interactive activities led by speaker Luqman Hakim S. Pd. The results of the seminar indicate an improvement in participants' understanding of the importance of moderation in maintaining harmony among religious communities, as well as their ability to formulate strategies to address challenges in implementing moderation values in daily life. The conclusion of this article emphasizes the importance of moderation seminars as a concrete step in shaping a young generation that is inclusive and tolerant in facing diversity in society. Abstrak Artikel ini membahas penerapan moderasi beragama melalui seminar yang dilaksanakan di Madrasah Aliyah (MA) Mazra'atul Ulum Paciran. Seminar tersebut bertujuan untuk meningkatkan pemahaman peserta tentang nilai-nilai toleransi dan moderasi dalam konteks keberagaman agama di Indonesia. Dengan menggunakan metode pendekatan kualitatif, seminar ini melibatkan seluruh siswa-siswi MA serta pihak sekolah dalam diskusi dan aktivitas interaktif yang dipimpin oleh pemateri Luqman Hakim S. Pd. Hasil dari seminar ini menunjukkan peningkatan pemahaman peserta tentang pentingnya moderasi dalam menjaga kerukunan antarumat beragama, serta kemampuan mereka dalam merumuskan strategi untuk menghadapi tantangan dalam mengimplementasikan nilai-nilai moderasi dalam kehidupan sehari-hari. Kesimpulan dari artikel ini menekankan pentingnya seminar moderasi sebagai langkah konkret dalam membentuk generasi muda yang inklusif dan toleran dalam menghadapi keragaman di masyarakat.